A Copper(I)–Arene Complex With an Unsupported η6 Interaction1. Issue 10 (21st January 2015) - Wright, Ashley M.; Irving, Benjamin J.; Wu, Guang; Meijer, Anthony J. H. M.; Hayton, Trevor W.
Abstract Addition of PR3 (R=Ph or OPh) to [Cu(η2‐Me6C6)2][PF6] results in the formation of [(η6‐Me6C6)Cu(PR3)][PF6], the first copper–arene complexes to feature an unsupported η6 arene interaction. A DFT analysis reveals that the preference for the η6 binding mode is enforced by the steric clash between the methyl groups of the arene ligand and the phenyl rings of the phosphine co‐ligand.